Respostas
respondido por:
1
Olá!!!
Resolução!!!
2m + 6 = m
2m - m = - 6
m = - 6
S = { - 6 }
Prova real
2m + 6 = m
2 • ( - 6 ) + 6 = - 6
- 12 + 6 = - 6
- 6 = - 6 OK!
Espero ter ajudado!!!
Resolução!!!
2m + 6 = m
2m - m = - 6
m = - 6
S = { - 6 }
Prova real
2m + 6 = m
2 • ( - 6 ) + 6 = - 6
- 12 + 6 = - 6
- 6 = - 6 OK!
Espero ter ajudado!!!
respondido por:
0
2m+6=m->>> Deixa letra de um lado e número de outro lado:
2m-m=-6
m=-6
2m-m=-6
m=-6
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás